Razzmatazz : a novel - Moore, Christopher, 1957- (Sammy and the Cheese, 2022)
"San Francisco, 1947. Bartender Sammy 'Two Toes' Tiffin and the rest of the Cookie's Coffee Irregulars, a ragtag bunch of working mugs last seen in Noir, are on the hustle: they're trying to open a driving school for Chinatown residents; shanghai an abusive Swedish stevedore; get Mable, the local madam, and her girls to a Christmas party at the State Hospital without alerting the overzealous head of the S.F.P.D. vice squad; all while Sammy's girlfriend, Stilton (a.k.a. the Cheese), and her 'Wendy the Welder' gal pals are using their wartime shipbuilding skills on a secret project that might be attracting the attention of some government Men in Black. And, oh yeah, someone is murdering the city's drag kings and club owner Jimmy Vasco is sure she's next on the list and wants Sammy to find the killer. Meanwhile, Eddie 'Moo Shoes' Shu has been summoned by his Uncle Ho to help save his opium den from Squid Kid Tang, a vicious gangster who is determined to retrieve a priceless relic: an ancient statue of the powerful Rain Dragon that Ho stole from one of the fighting tongs forty years earlier. And if Eddie blows it, he just might call down the wrath of that powerful magical creature on all of Fog City."--